Te Ara a Kiwa - Stevens, Michael J. (Historian) (Te Rūnaka o Awarua, 2022)
A comic about the creation of Te Ara-a-Kiwa by Kiwa for his wife, Hinemoana, after Māui hauls his great fish out of the ocean.